Impact of the Bronx Community Health Leaders Program for Socioeconomically Disadvantaged Prehealth Students (Mary Ann Liebert, 2021)
Purpose: Underrepresentation of racial and ethnic minorities in the health care workforce is a local and national issue. We describe and report on outcomes of a longitudinal service-driven prehealth pathway program in a low-income community intended to address this disparity and increase health equity. Methods: The Bronx Community Health Leaders (BxCHL) is a prehealth pathway program for socioeconomically disadvantaged and underrepresented minority students seeking careers in health care. The program enrolls students in college or college graduates and provides longitudinal near-peer mentorship, exposure to the health care environment, and supports professional development. An academic federally qualified health center serves as the program's home site and learning environment. We conducted surveys and tracked the career advancement of program participants over a 6-year period, 2014?2020. Results: One hundred sixty-eight students participated in BxCHL for >3 months. Of these, 76 students advanced into professional health career programs with 39 direct acceptances and 15 conditional acceptances to medical school programs, 9 nursing, 4 physician assistant, 9 health-related masters level programs, 1 respiratory therapy, and 1 optometry. The direct and overall acceptance (direct and conditional) rate of medical school applicants is 59% and 86%, respectively. The first 11 BxCHL alumni obtained their medical degree. Conclusions: BxCHL's longitudinal service-driven and near-peer mentorship program design represents a replicable model to address health equity by supporting prehealth students from communities with limited access to mentors and professional learning environments in entering the health care workforce and serving their communities of origin.